Association of dietary patterns with diabetes-related comorbidities varies among diabetes endotypes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zhu, Anna; Zaharia, Oana-Patricia; Strom, Alexander; Bönhof, Gidon J.; Goletzke, Janina; Trenkamp, Sandra; Wagner, Robert; et al. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Ernährung und Alltagsbewältigung - Ein Spannungsfeld für Individuum, Haushalt und Gesellschaft - Buyken, Anette; Libuda, Lars (DGEwissen)

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Haushaltswissenschaft – Eine Diskussionsgrundlage - Küster, Christine; Klünder, Nina; Wagenknecht, Inga (Hauswirtschaft und Wissenschaft)

Wirtschaft neu ausrichten. Care-Initiativen in Deutschland, Österreich und der Schweiz.

Alternative für alle? Inklusionsspezifische Analyse der AfD und ihrer Wähler*innen - Freymuth, Nina (Diskriminierungsprozesse und Teilhabeperspektiven - Herausforderungen für die Praxis der Inklusion. Ausgewählte Master-Thesen 2018-2022 des Masterstudiengangs "Soziale Inklusion: Gesundheit und Bildung" der Evangelischen Hochschule Rheinland-Westfalen-Lippe)

Work-related stressors and coping behaviors among leaders in small and medium-sized IT and technological services enterprises - Dannheim, Indra; Buyken, Anette; Kroke, Anja (BMC Public Health)
Abstract Background Occupational health interventions for leaders are underrepresented in small and medium-sized enterprises (SMEs). When creating and developing effective occupational health interventions, identification of the specific needs of the target group is regarded as an essential step before planning an intervention. Therefore, the aim of this study was (1) to examine the subjectively experienced work-related stressors of leaders in small and medium-sized IT and technological services enterprises, (2) to explore coping behaviors leaders use to deal with the experienced work-related stressors, (3) to investigate resources supporting the coping process and (4) to identify potentially self-perceived consequences resulting from the experienced stressors. Methods Ten semi-structured interviews with leaders in small and medium-sized IT and technological services enterprises were conducted. The interviews were transcribed and analyzed with content-structuring qualitative content analysis in accordance to Kuckartz. Results Leaders in small and medium-sized IT and technological services enterprises experience various stressors caused by work organization as well as industry-related stressors and other work-related stressors. To address the experienced stressors, leaders apply problem focused coping behaviors (e.g. performing changes on structural and personal level), emotional focused coping behaviors (e.g. balancing activities, cognitive restructuring) as well as the utilization of social support. Helpful resources for the coping process include organizational, social and personal resources. As a result of the experienced work-related stressors, interviewees stated to experience different health impairments, negative effects on work quality as well as neglect of leisure activities and lack of time for family and friends. Conclusion The identified experienced work-related stressors, applied coping behaviors, utilized resources and emerging consequences underpin the urgent need for the development and performance of health-oriented leadership interventions for leaders in small and medium- sized IT and technological services. The results of this study can be used when designing a target-oriented intervention for the examined target group.
Keywords: Public Health; Environmental and Occupational Health

Choice architecture interventions promoting sustained healthier food choice and consumption by students in a secondary school setting: A systematic review of intervention studies - Schulte, Eva A.; Winkler, Gertrud; Brombach, Christine; Buyken, Anette (Public Health Nutrition)
Abstract Objective: To systematically review the impact of choice architecture interventions (CAI) on the food choice of healthy adolescents in a secondary school setting. Factors potentially contributing to the effectiveness of CAI types and numbers implemented and its long-term success were examined. Design: PUBMED and Web of Science were systematically searched in October 2021. Publications were included following predefined inclusion criteria and grouped according to number and duration of implemented interventions. Intervention impact was determined by systematic description of the reported quantitative changes in food choice and/or consumption. Intervention types were compared with regards to food selection and sustained effects either during or following the intervention. Setting: CAI on food choice of healthy adolescents in secondary schools. Participants: Not applicable Results: Fourteen studies were included; four randomized controlled trials and five each of controlled or uncontrolled pre-post design, respectively. Four studies implemented a single CAI type, with ten implementing > 1. Three studies investigated CAI effects over the course of a school year either by continuous or repeated data collection, while ten studies’ schools were visited on selected days during intervention. Twelve studies reported desired changes in overall food selection, yet effects were not always significant, and appeared less conclusive for longer term studies. Conclusions: This review found promising evidence that CAI can be effective in encouraging favorable food choices in healthy adolescents in a secondary school setting. However, further studies designed to evaluate complex interventions are needed.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).
Keywords: Nutrition and Dietetics; General Medicine; Medicine (miscellaneous)

Full Breastfeeding and Allergic Diseases—Long-Term Protection or Rebound Effects? - Libuda, Lars; Filipiak-Pittroff, Birgit; Standl, Marie; Schikowski, Tamara; von Berg, Andrea; Koletzko, Sibylle; Bauer, Carl-Peter; Heinrich, Joachim; Berdel, Dietrich; Gappa, Monika (Nutrients)
A previous follow-up of the GINIplus study showed that breastfeeding could protect against early eczema. However, effects diminished in adolescence, possibly indicating a “rebound effect” in breastfed children after initial protection. We evaluated the role of early eczema until three years of age on allergies until young adulthood and assessed whether early eczema modifies the association between breastfeeding and allergies. Data from GINIplus until 20-years of age (N = 4058) were considered. Information on atopic eczema, asthma, and rhinitis was based on reported physician’s diagnoses. Adjusted Odds Ratios (aOR) were modelled by using generalized estimating equations. Early eczema was associated with eczema (aORs = 3.2–14.4), asthma (aORs = 2.2–2.7), and rhinitis (aORs = 1.2–2.7) until young adulthood. For eczema, this association decreased with age (p-for-interaction = 0.002–0.006). Longitudinal models did not show associations between breastfeeding and the respective allergies from 5 to 20 years of age. Moreover, early eczema generally did not modify the association between milk feeding and allergies except for rhinitis in participants without family history of atopy. Early eczema strongly predicts allergies until young adulthood. While preventive effects of full breastfeeding on eczema in infants with family history of atopy does not persist until young adulthood, the hypothesis of a rebound effect after initial protection cannot be confirmed.
Keywords: Food Science; Nutrition and Dietetics

Ernährungsarmut unter Pandemiebedingungen - Birner, Regina; Linseisen, Jakob; Arens-Azevedo, Ulrike; Balmann, Alfons; Biesalski, Hans Konrad; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kay-Uwe; Iweala, Sarah; Martínez, José; et al. (Berichte über Landwirtschaft)
Ernährungsarmut wird als Problem in Deutschland weitgehend vernachlässigt. Von materieller Ernährungsarmut betroffen sind Menschen, denen es aufgrund fehlender finanzieller Mittel nicht möglich ist, sich gesundheitsfördernd zu ernähren. Etwa 3,5 % der Bevölkerung (rund drei Millionen Menschen) sind durch materielle Ernährungsarmut gefährdet. Damit einher geht oft auch soziale Ernährungsarmut, die Menschen von der sozialen Teilhabe ausschließt, die z. B. durch gemeinsames Essen ermöglicht wird. Essen ist nicht nur von Bedeutung für die körperliche Gesundheit, sondern auch zentral für die psychische Gesundheit und das Wohlbefinden sowie für die soziale Zugehörigkeit, was sich wiederum auf die körperliche Gesundheit auswirkt. Die sozialen Funktionen des Essens werden vielfach übersehen – und bei der Berechnung des Regelbedarfs ausgeblendet. Gerade die Corona-Pandemie hat gezeigt, wie fehlende soziale Kontakte und sozialer Ausschluss sich auf die physische, psychische und soziale Gesundheit auswirken können. Aus Sicht des WBAE (Wissenschaftliche Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucherschutz) ist deshalb der integrative Blick auf die materielle und soziale Ernährungsarmut zentral, da sie sich gegenseitig verstärken können. Diese Stellungnahme befasst sich mit der Frage, wie sich die Corona-Pandemie auf von Ernährungsarmut gefährdete Menschen ausgewirkt hat und was daraus gelernt werden kann. Ein wichtiger Aspekt ist der zeitweilige Wegfall von Essensangeboten in Kitas, Schulen, Tafeln und anderen karitativen Essensangeboten, die ein Sicherheitsnetz für Menschen in Ernährungsarmut darstellen. Die Stellungnahme zieht auf dieser Basis auch Schluss-folgerungen zur Ernährungsarmut außerhalb von Pandemiebedingungen. Im Hinblick auf die Notwendigkeit der Vermeidung von Fehlernährung in Haushalten, die von Ernährungsarmut bedroht sind, kommt der WBAE zu dem Schluss, dass diese Risikogruppe während der Pandemie nicht ausreichend im Fokus der Maßnahmen zur Abmilderung der Pandemiefolgen stand. Dies zeigt sich schon daran, dass kaum Daten erhoben wurden. Deutschland verfügt über kein klares Indikatoren- und Zielsystem und kein Monitoring zur Ernährungsarmut. Die wenigen vorhandenen Daten weisen auf problematische Entwicklungen hin. Insgesamt wurden durch den Bund sehr umfangreiche Mittel zur Bewältigung der wirtschaftlichen und sozialen Folgen der Corona-Pandemie und zur Einkommenssicherung während der Pandemie eingesetzt. Dies ist unter dem Blickwinkel „Ernährungsarmut” positiv zu bewerten. Es ist davon auszugehen, dass diese Maßnahmen verhindert haben, dass noch mehr Haushalte von Ernährungsarmut betroffen waren. Insgesamt zeigt die Analyse jedoch, dass es kaum gezielte Maßnahmen gab, um den Ausfall von Kita- und Schulernährung durch alternative Formen der Bereitstellung von Lebensmitteln oder einer warmen Mahlzeit aufzufangen. Maßnahmen auf Bundesebene fehlten, um Länder, Kommunen und nicht-staatliche Organisationen dabei zu unterstützen. Auswertungen der Pandemiemaßnahmen vergleichbarer Länder zeigen, dass dort schnelle und flexible Maßnahmen zur Bereitstellung von Lebensmitteln eine wichtige Rolle gespielt haben, um armutsgefährdete Haushalte zu unterstützen. In Deutschland wurden vorwiegend finanzielle Transfers genutzt, z. T. zeitlich verzögert und wenig zielgruppenspezifisch. Vor diesem Hintergrund hat der WBAE mögliche Maßnahmen gegen Ernährungsarmut – in Krisen, aber auch generell – untersucht: (1) finanzielle Transfers (einmalig oder fortlaufend), (2) Lebensmittelgutscheine („Voucher“), (3) Lebensmittelpakete und (4) warme Mahlzeiten, wobei die letzten beiden Optionen jeweils zur Abholung oder zur Auslieferung angeboten werden können. Die untersuchten internationalen Beispiele zeigen Möglichkeiten, wie z. T. mit schnellen und teilweise innovativen Ansätzen auf Lockdown-Maßnahmen reagiert wurde. Im Grundsatz spricht aus Sicht des WBAE aber vieles für das deutsche System zur Bekämpfung der Ernährungsarmut, das im Kern auf einem Bürgergeld beruht. Ein solches Bürgergeld muss jedoch ausreichend sein, um materielle und soziale Ernährungsarmut zu vermeiden. Die aktuellen, im Bürgergeld für Essen und Getränke zur Verfügung stehenden Beträge entsprechen allerdings nicht diesem Anspruch. Bei der Einführung des Bürgergelds im Jahr 2023 wurde zwar zeitnah auf die hohe Inflation reagiert. Die Berechnungsmethodik für die Bedarfsermittlung wurde aber nicht angepasst, sodass der Regelsatz nach wie vor nicht für eine gesundheitsfördernde Ernährung ausreicht. Die soziale Funktion von Ernährung wird bei der Berechnung des Regelsatzes nicht berücksichtigt. Um bei akutem Handlungsbedarf, wie z. B. auch bei der derzeitigen Inflation, schneller reagieren zu können, sollten außerdem Systeme zur Auszahlung sozial differenzierter „Krisentransfers” an vulnerable Haushalte mit geringem Verwaltungsaufwand ermöglicht werden. Darüber hinaus sollte für den zentralen Bereich der Kinder-ernährung der Schutz einer adäquaten Grundsicherung durch einen Systemwechsel zu einer integrativen, beitragsfreien und somit nicht-diskriminierenden Kita- und Schulverpflegung ergänzt werden, die zudem den DGE-Qualitätsstandards entspricht. Schließlich sollte der Staat privates, ehrenamtliches Engagement ergänzend fördern, z. B. durch Infrastrukturunterstützung bei karitativen Essensangeboten. Eine Herausforderung der Gestaltung von karitativen Lebensmittelangeboten besteht darin, dass sie oft als stigmatisierend und beschämend wahrgenommen werden und der Nachweis eines Anspruches teils schwierig ist. Zudem bestehen oft nur wenige Wahlmöglichkeiten, sodass individuelle Präferenzen oder Unverträglichkeiten nur sehr eingeschränkt berücksichtigt werden können. Im Hinblick auf die soziale Dimension der Ernährung kommt hinzu, dass wichtige soziale Funktionen des Essens, wie das gemeinsame Essen, also Kommensalität, nicht oder nur sehr eingeschränkt ermöglicht wird. Auch bleiben diejenigen, die versorgt werden, dabei meist unter sich. Vor dem Hintergrund dieser Gesamteinschätzung empfiehlt der WBAE die folgenden, in Abbildung Z 1 dargestellten Maßnahmen (siehe Beitrag). Zusammenfassend betont der WBAE die in Deutschland weiterhin unterschätzten Risiken materieller und sozialer Ernährungsarmut. Im Rahmen der geplanten Nationalen Ernährungsstrategie der Bundesregierung sollte dem Thema Ernährungsarmut aus Sicht des WBAE eine herausgehobene Bedeutung zugemessen werden.

Perspective: A Conceptual Framework for Adaptive Personalized Nutrition Advice Systems - Renner, Britta; Buyken, Anette; Gedrich, Kurt; Lorkowski, Stefan; Watzl, Bernhard; Linseisen, Jakob; Daniel, Hannelore; Conrad, Johanna; Ferrario, Paola G.; Holzapfel, Christina; Leitzmann, Michael; Richter, Margrit; et al. (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Plant-based dietary patterns and cardiometabolic risk factors in subgroups of individuals with diabetes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zaharia, Oana P.; Goletzke, Janina; Buyken, Anette; Trenkamp, Sandra; Wagner, Robert; Lieb, Wolfgang; Roden, Michael; et al. (Diabetologie und Stoffwechsel)

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Spiller, Achim; Nieberg, Hiltrud; Renner, Britta; Balmann, Alfons; Birna, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kai-Uwe; Linseisen, Jakob; Nöthlings, Ute; et al.
Zitieren als: Wissenschaftlicher Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucher- schutz beim BMEL (2023): Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen. Gutachten. Berlin.

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Zum Einstieg: Master-Arbeit zu ökologischer und sozial gerechter Stadtplanung. Ein fiktives Beispiel - Freymuth, Nina (Wissenschaftsläden in der Sozialen Arbeit. Partizipative Forschung und soziale Innovationen)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Professionalisierung von Lehramtsstudierenden für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft - Dehn, Freya; Meyer, Anja; Niederhaus, Constanze; Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Aufgrund der heterogenen Schülerschaft im Berufsfeld Ernährung und Hauswirtschaft müssen Studierende für sprachbildenden Fachunterricht professionalisiert werden. Aufbauend auf einer theoretischen Fundierung werden konkrete Umsetzungsbeispiele anhand von drei exemplarischen Online-Modulen für den Ausbildungsberuf Hotelfachfrau/-mann vorgestellt.

Dietary Glycaemic Index Labelling: A Global Perspective. - Barclay, AW; LSA, Augustin; Brighenti, F; Delport, E; Henry, CJ; Sievenpiper, JL; Usic, K; Yuexin, Y; Zurbau, A; TMS, Wolever; Astrup, A; Bulló, M; et al. (Nutrients)

Increased Prevalence of Subclinical Hypothyroidism and Thyroid Autoimmunity in Depressed Adolescents - Hirtz, Raphael; Focker, Manuel; Libuda, Lars; Antel, Jochen; Ozturk, Dana; Kiewert, Cordula; Munteanu, Martin; Peters, Triinu; Fuhrer, Dagmar; Zwanziger, Denise; Thamm, Michael; Hebebrand, Johannes; et al. (The Journal of Clinical Psychiatry)

Rapid amelioration of anorexia nervosa in a male adolescent during metreleptin treatment including recovery from hypogonadotropic hypogonadism - Antel, Jochen; Tan, Susanne; Grabler, Marvin; Ludwig, Christine; Lohkemper, Dominik; Brandenburg, Tim; Barth, Nikolaus; Hinney, Anke; Libuda, Lars; Remy, Miriam; Milos, Gabriella; Hebebrand, Johannes (European Child & Adolescent Psychiatry)
Abstract With this case report we support our medical hypothesis that metreleptin treatment ameliorates starvation related emotional, cognitive and behavioral symptomatology of anorexia nervosa (AN) and show for the first time strong effects in a male patient with AN. A 15.9 year old adolescent with severe AN of eight-month duration was treated off-label with metreleptin. Hyperactivity was assessed with accelerometry. Visual analogue scales (VAS), validated self- and clinician rating scales and lab results tracked changes from baseline to end of the 24-day dosing period and a five-month follow-up. Substantial improvements of mood and eating disorder related cognitions and hyperactivity set in after two days of treatment. During dosing, sub-physiological testosterone and TT3 levels normalized; clinically libido reemerged. Weight did not increase substantially during the dosing period. During follow-up target weight was attained; mood did not deteriorate; hyperactivity ceased. The results substantiate the strong effects seen in female cases and underscore the need for a double-blind placebo-controlled trial to confirm the observed strong, multiple and rapid onset beneficial effects of metreleptin in AN.

Befähigung zur Reflexion und zum Umgang mit Ambiguitäten. Zur Wirksamkeit von Unterricht für "Lebensführung" - Schlegel-Matthies, Kirsten; Wespi, Claudia (Wirksamer Fachunterricht. Eine metaanalytische Betrachtung von Expertisen aus 17 Schulfächern)

Wirksamer Unterricht für Lebensführung. (Unterrichtsqualität: Perspektiven von Expertinnen und Experten 12) - Schlegel-Matthies, Kirsten; Wespi, Claudia

Wörterbuch. Soziale Arbeit - Klünder, Nina (Wörterbuch. Soziale Arbeit)

Relevance of fructose intake in adolescence for fatty liver indices in young adulthood - Perrar, Ines; Buyken, Anette; Penczynski, Katharina J.; Remer, Thomas; Kuhnle, Gunter G.; Herder, Christian; Roden, Michael; Della Corte, Karen; Nöthlings, Ute; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose To examine the association between fructose intake in adolescence and fatty liver indices (hepatic steatosis index (HSI), fatty liver index (FLI)) in young adulthood. Methods Overall, 246 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had a fasting blood sample in adulthood (18–36 years), at least two 3-day weighed dietary records for calculating fructose intakes and other fructose-containing sugars (total (TS), free (FS), added sugar (AS)) as well as two complete 24-h urine samples for calculating sugar excretion (fructose excretion (FE), fructose + sucrose excretion (FE + SE)) in adolescence (males: 9.5–16.5 years; females: 8.5–15.5 years) were analysed using multivariable linear regression analyses. Results On the level of dietary intake, no prospective associations were observed between adolescent fructose intake and both adult fatty liver indices, whereas higher FS intakes were associated with lower levels of HSI ( P trend = 0.02) and FLI ( P trend = 0.03). On the urinary excretion level, however, a higher FE (P trend = 0.03) and FE + SE ( P trend = 0.01) in adolescence were prospectively related to higher adult FLI values. No associations were observed between adolescent sugar excretion and adult HSI. Conclusion The present study does not provide unambiguous support for a detrimental impact of adolescent fructose intake on adult liver health. Nonetheless, further examinations estimating exposure by means of urinary excretion as well as dietary intake levels appear warranted.

The Prospective Association of Dietary Sugar Intake in Adolescence With Risk Markers of Type 2 Diabetes in Young Adulthood - Della Corte, Karen A.; Penczynski, Katharina; Kuhnle, Gunter; Perrar, Ines; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Remer, Thomas; Alexy, Ute; Buyken, Anette (Frontiers in Nutrition)
Purpose: To examine the prospective relevance of dietary sugar intake (based on dietary data as well as urinary excretion data) in adolescent years for insulin sensitivity and biomarkers of inflammation in young adulthood. Methods: Overall 254 participants of the DONALD study who had at least two 3-day weighed dietary records for calculating intakes of fructose, glucose, sucrose, total, free, added sugars, total sugars from sugar-sweetened beverages (SSB), juice, and sweets/sugar or at least two complete 24 h urine samples ( n = 221) for calculating sugar excretion (urinary fructose and urinary fructose + sucrose) in adolescence (females: 9–15 years, males: 10–16 years) and a fasting blood sample in adulthood (18–36 years), were included in multivariable linear regression analyses assessing their prospective associations with adult homeostasis model assessment insulin sensitivity (HOMA2-%S) and a pro-inflammatory score (based on CRP, IL-6, IL-18, leptin, chemerin, adiponectin). Results: On the dietary intake level, no prospective associations were observed between adolescent fructose, sucrose, glucose, added, free, total sugar, or total sugar from SSB, juice or sweets/sugar intake and adult HOMA2-%S ( p > 0.01). On the urinary level, however, higher excreted fructose levels were associated with improved adult HOMA2-%S ( p = 0.008) among females only. No associations were observed between dietary or urinary sugars and the adult pro-inflammatory score ( p > 0.01). Conclusion: The present study did not provide support that dietary sugar consumed in adolescence is associated with adult insulin sensitivity. The one potential exception was the moderate dietary consumption of fructose, which showed a beneficial association with adult fasting insulin and insulin sensitivity.

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Krüger, Bettina; Nöthlings, Ute; Buyken, Anette E.; Alexy, Ute (European Journal of Clinical Nutrition)
Abstract Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at baseline, 45% females) having at least two measures of chronotype and anthropometry ( N = 572). Chronotype was assessed with the Munich Chronotype Questionnaire and defined as: midpoint of sleep corrected for sleep-debt (MSFsc) accumulated over the week (later MSFsc represents later chronotype). Social jetlag (SJL) defines the difference between midpoint of sleep during week and weekend. Calculations for Fat Free Mass Index (FFMI [kg/m 2 )]) and Fat Mass Index (FMI) [kg/m 2 )]) were based on body fat percentage, weight, and height. To analyze the associations, we used linear mixed-effect regression models. Finally, the total cohort was split into three biologically relevant age groups (cut-off set at <12 years, ≥12 to ≤15 years and >15 years). Results Median follow-up was 2.1 years. Overall, change toward a later chronotype was significantly related with an increase in FMI (ß: 0.05, 95% CI: 0.01–0.08). A 1 h increase in social jetlag predicted an increase in BMI-SDS of 0.08 SDS units (95% CI: 0.01–0.14) and in FMI of 0.04 kg/m2 (95% CI: 0.003–0.08). Associations were stronger for the age group ≥12 to ≤15 years ( p for interaction: <0.001). No relationship was found with FFMI. Conclusions Changes in MSFsc and SJL during adolescence were associated with concurrent changes in BMI-SDS and FMI. The age ≥12 to ≤15 years appears to be a sensitive period in which chronobiological changes were clearly associated with increasing body fatness.

Ebenen der genetischen Analyse komplexer Phänotypen am Beispiel der Anorexia nervosa und der Varianz des Körpergewichts - Hirtz, Raphael; Zheng, Yiran; Rajcsanyi, Luisa S.; Libuda, Lars; Antel, Jochen; Peters, Triinu; Hebebrand, Johannes; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Genetische Varianten beeinflussen die Gewichtsregulation und die Entwicklung von Essstörungen. Zunächst haben familienbasierte, sogenannte formalgenetische Studien den erblichen Anteil an der Gewichtsregulation und an der Ätiologie von Essstörungen beleuchtet. In einer Vielzahl von Studien zeigten sich sowohl für die Varianz des Körpergewichts als auch für die Entstehung von Essstörungen Erblichkeitsschätzer (Heritabilitätsraten) von über 50 %. Mit diesem Wissen begab man sich in den 90er-Jahren des letzten Jahrhunderts auf die Suche nach den zugrundeliegenden Genen (genauer: genetischen Varianten), die das Körpergewicht, das Essverhalten oder beide Phänotypen auf Grundlage geteilter Mechanismen beeinflussen. Zunächst wurden Kandidatengenstudien durchgeführt. Dabei untersuchte man auf Grundlage unterschiedlicher, v. a. aber pathophysiologisch plausibler Überlegungen Gene mit hoher Relevanz für die untersuchten Phänotypen. Dieser Ansatz war für Essstörungen nicht sehr erfolgreich, für die Gewichtsregulation konnte eine Handvoll Gene identifiziert werden. Verbunden mit großen methodischen Fortschritten in der genetischen Forschung und v. a. der Etablierung sogenannter genomweiter Assoziationsstudien (GWAS) Anfang der 2000er-Jahre konnten bislang über 1000 Varianten/Genorte detektiert werden, die das Körpergewicht beeinflussen. Für die Essstörung Anorexia nervosa (AN) sind aktuell acht solcher Genorte beschrieben. Diese Ergebnisse, aber auch aktuelle Ansätze zu phänotypübergreifenden Analysen lassen Einblicke in die komplexe Regulation des Körpergewichtes zu und haben zudem unerwartete Pathomechanismen für AN aufgezeigt.

Ernährungseffekten auf der Spur – Wie die Genetik helfen kann, Zusammenhänge zwischen Ernährung und seelischer Gesundheit aufzudecken - Libuda, Lars; Hebebrand, Johannes; Föcker, Manuel; Peters, Triinu; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)
Zusammenfassung. Einleitung: Klassische ernährungsepidemiologische Studien (Beobachtungsstudien und randomisierte Interventionsstudien) zeigen, dass die Ernährung ein wichtiger Ansatzpunkt für die Prävention und Therapie psychischer Störungen sein könnte. Diese Studientypen haben allerdings Limitationen, die bei der Ergebnisinterpretation berücksichtigt werden müssen. In dieser narrativen übersichtsarbeit wird beschrieben, wie genetische Studien ein Bindeglied darstellen können, um einen Zusammenhang zwischen Ernährung und psychischen Störungen herzustellen. Methodik: Im Artikel werden verschiedene Ansätze genetischer phänotypübergreifender Analysen sowie Beispiele für deren Anwendungen in der ernährungspsychiatrischen Forschung beschrieben. Darüber hinaus werden spezifische Voraussetzungen sowie Stärken und Schwächen diskutiert. Ergebnisse: Als Methoden genetischer phänotypübergreifender Analysen sind im Rahmen ernährungspsychiatrischer Forschung bislang genetische Korrelationsanalysen, Look-up-Analysen sowie Mendelsche Randomisierungsstudien (MR-Studien) eingesetzt worden. Genetische Korrelationsanalysen und Look-up-Analysen geben erste Hinweise auf mögliche genetische überlappungen zwischen einer psychischen Störung und einem Stoffwechselweg und/oder der Versorgung mit einem spezifischen Nährstoff. MR-Studien sind weitergehende Detailanalysen mit dem Ziel, Kausalzusammenhänge zu identifizieren, beinhalten allerdings sehr spezifische Grundvoraussetzungen für ihre Durchführung. Schlussfolgerung: Genetische phänotypübergreifende Analysen sind eine sinnvolle Ergänzung der klassischen Ernährungsepidemiologie. Insbesondere signifikante Ergebnisse von MR-Studien sind eine wichtige Grundlage zur Entwicklung geeigneter Ernährungsinterventionen, die in nachfolgenden randomisiert kontrollierten Interventionsstudien mit deutlich erhöhter Erfolgsaussicht getestet werden können. Sie sind somit wichtige Instrumente einer effizienten ernährungspsychiatrischen Forschung.

Lack of Evidence for a Relationship Between the Hypothalamus-Pituitary-Adrenal and the Hypothalamus-Pituitary-Thyroid Axis in Adolescent Depression - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Antel, Jochen; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Endocrinology)
In adults with major depressive disorder (MDD), a dysfunction between the hypothalamus-pituitary-adrenal (HPA) and the hypothalamus-pituitary-thyroid (HPT) axis has been shown, but the interaction of both axes has not yet been studied in adolescent major depressive disorder (MDD). Data from 273 adolescents diagnosed with MDD from two single center cross-sectional studies were used for analysis. Serum levels of thyrotropin (TSH), free levothyroxine (fT4), and cortisol were determined as indicators of basal HPT and HPA axis functioning and compared to that of adolescent controls by t-tests. Quantile regression was employed in the sample of adolescents with MDD to investigate the relationship between both axes in the normal as well as the pathological range of cortisol levels, considering confounders of both axes. In adolescent MDD, cortisol levels and TSH levels were significantly elevated in comparison to controls ( p = <.001, d = 1.35, large effect size, and p = <.001, d = 0.79, moderate effect size, respectively). There was a positive linear relationship between TSH and cortisol ( p = .003, d = 0.25, small effect size) at the median of cortisol levels (50 th percentile). However, no relationship between TSH and cortisol was found in hypercortisolemia (cortisol levels at the 97.5 th percentile). These findings imply that HPT and HPA axis dysfunction is common in adolescents with MDD and that function of both axes is only loosely related. Moreover, the regulation of the HPA and HPT axis are likely subjected to age-related maturational adjustments since findings of this study differ from those reported in adults.

Relevance of dietary glycemic index, glycemic load and fiber intake before and during pregnancy for the risk of gestational diabetes mellitus and maternal glucose homeostasis - Zhang, Xiao; Gong, Yunhui; Della Corte, Karen; Yu, Dianke; Xue, Hongmei; Shan, Shufang; Tian, Guo; Liang, Yi; Zhang, Jieyi; He, Fang; Yang, Dagang; Zhou, Rong; et al. (Clinical Nutrition)

Early life factors and their relevance for markers of cardiometabolic risk in early adulthood - Nyasordzi, Juliana; Conrad, Johanna; Goletzke, Janina; Ludwig-Walz, Helena; Herder, Christian; Roden, Michael; Wudy, Stefan A.; Hua, Yifan; Remer, Thomas; Buyken, Anette (Nutrition, Metabolism and Cardiovascular Diseases)

International tables of glycemic index and glycemic load values 2021: a systematic review - Atkinson, Fiona S; Brand-Miller, Jennie C; Foster-Powell, Kaye; Buyken, Anette; Goletzke, Janina (The American Journal of Clinical Nutrition)
ABSTRACT Background Reliable tables of glycemic indexes (GIs) and glycemic loads (GLs) are critical to research examining the relationship between glycemic qualities of carbohydrate in foods, diets, and health. In the 12 years since the last edition of the tables, a large amount of new data has become available. Objectives To systematically review and tabulate published and unpublished sources of reliable GI values, including an assessment of the reliability of the data. Methods This edition of the tables lists over 4000 items, a 61% increase in the number of entries compared to the 2008 edition. The data have been separated into 2 lists. The first represents more precise values derived using the methodology recommended by the International Standards Organization (∼2100 items). The second list contains values determined using less robust methods, including using limited numbers of healthy subjects or with a large SEM (∼1900 food items). Results Dairy products, legumes, pasta, and fruits were usually low-GI foods (≤55 on the 100-point glucose scale) and had consistent values around the world. Cereals and cereal products, however, including whole-grain or whole-meal versions, showed wide variation in GI values, presumably arising from variations in manufacturing methods. Breads, breakfast cereals, rice, savory snack products, and regional foods were available in high-, medium-, and low-GI versions. Most varieties of potato were high-GI foods, but specific low-GI varieties have now been identified. Conclusions The availability of new data on the GIs of foods will facilitate wider research and application of the twin concepts of GI and GL. Although the 2021 edition of the tables improves the quality and quantity of GI data available for research and clinical practice, GI testing of regional foods remains a priority. This systematic review was registered in PROSPERO as #171204.

Maternal pregnancy weight or gestational weight gain and offspring's blood pressure: A systematic review - Ludwig-Walz, Helena; Nyasordzi, Juliana; Weber, Katharina S.; Buyken, Anette; Kroke, Anja (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Size Matters: The CAG Repeat Length of the Androgen Receptor Gene, Testosterone, and Male Adolescent Depression Severity - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Psychiatry)
There is a distinct increase in the prevalence of depression with the onset of puberty. The role of peripubertal testosterone levels in boys in this context is insufficiently understood and may be modulated by a functional polymorphism of the androgen receptor gene (AR), a variable number of CAG repeats. Moreover, there is preliminary evidence that the relationship between testosterone, CAG repeat length, and the severity of depressive symptoms may differ between subclinical and overt depression, but this has neither been studied in a clinical sample of adolescents with depression nor compared between subclinical and overt depression in an adequately powered study. To investigate the relationship between free testosterone, CAG repeat length of the AR, depression status (subclinical vs. overt), and the severity of depressive symptoms, 118 boys treated as in- or daycare patients at a single psychiatric hospital were studied. Of these, 73 boys had at least mild depressive symptoms according to the Beck Depression Inventory-II (BDI-II > 13). Higher-order moderation analysis in the multiple regression framework revealed a constant relationship between free testosterone and depression severity irrespective of the number of CAG repeats in adolescents with a BDI-II score ≤ 13. In adolescents with a BDI-II score > 13, however, there was a significant negative relationship between free testosterone and BDI-II score in patients with <19 CAG repeats and a significant positive relationship regarding free testosterone and BDI-II score in those with more than 28 CAG repeats, even when considering important covariates. These results suggest that the effects of testosterone on mood in male adolescents with depression depend on the genetic make-up of the AR as well as on depression status. This complex relationship should be considered by future studies addressing mental health issues against an endocrine background and may, moreover, contribute to tailored treatment concepts in psychiatric medicine, especially in adults.

Vitamin D Level Trajectories of Adolescent Patients with Anorexia Nervosa at Inpatient Admission, during Treatment, and at One Year Follow Up: Association with Depressive Symptoms - Föcker, Manuel; Timmesfeld, Nina; Bühlmeier, Judith; Zwanziger, Denise; Führer, Dagmar; Grasemann, Corinna; Ehrlich, Stefan; Egberts, Karin; Fleischhaker, Christian; Wewetzer, Christoph; Wessing, Ida; Seitz, Jochen; et al. (Nutrients)
(1) Background: Evidence has accumulated that patients with anorexia nervosa (AN) are at higher risk for vitamin D deficiency than healthy controls. In epidemiologic studies, low 25(OH) vitamin D (25(OH)D) levels were associated with depression. This study analyzed the relationship between 25(OH)D serum levels in adolescent patients and AN and depressive symptoms over the course of treatment. (2) Methods: 25(OH)D levels and depressive symptoms were analyzed in 93 adolescent (in-)patients with AN from the Anorexia Nervosa Day patient versus Inpatient (ANDI) multicenter trial at clinic admission, discharge, and 1 year follow up. Mixed regression models were used to analyze the relationship between 25(OH)D levels and depressive symptoms assessed by the Beck Depression Inventory (BDI-II). (3) Results: Although mean 25(OH)D levels constantly remained in recommended ranges (≥50 nmol/L) during AN treatment, levels decreased from (in)patient admission to 1 year follow up. Levels of 25(OH)D were neither cross-sectionally, prospectively, nor longitudinally associated with the BDI-II score. (4) Conclusions: This study did not confirm that 25(OH)D levels are associated with depressive symptoms in patients with AN. However, increasing risks of vitamin D deficiency over the course of AN treatment indicate that clinicians should monitor 25(OH)D levels.

Alterations in B cell subsets correlate with body composition parameters in female adolescents with anorexia nervosa - Freff, Jana; Schwarte, Kathrin; Bröker, Lisa; Bühlmeier, Judith; Kraft, Isabelle; Öztürk, Dana; Hinney, Anke; Arolt, Volker; Dannlowski, Udo; Romer, Georg; Baune, Bernhard T.; Hebebrand, Johannes; et al. (Scientific Reports)
Abstract Anorexia nervosa (AN) is a severe eating disorder and often associated with altered humoral immune responses. However, distinct B cell maturation stages in peripheral blood in adolescents with AN have not been characterized. Treatment effects and the relationship between clinical and B cell parameters are also not fully understood. Here we investigated the phenotype of circulating B cell subsets and the relationship with body composition in adolescents with AN before (T0, n = 24) and after 6 weeks (T1, n = 20) of treatment. Using multi-parameter flow cytometry, we found increased percentages of antigen-experienced B cells and plasmablasts in patients with AN compared to healthy controls (n = 20). In contrast, percentages of CD1d + CD5 + B cells and transitional B cells with immunoregulatory roles were reduced at T0 and T1. These B cell frequencies correlated positively with fat mass, fat mass index (FMI), free fat mass index, and body mass index standard deviation score. In addition, scavenger-like receptor CD5 expression levels were downregulated on transitional B cells and correlated with fat mass and FMI in AN. Our findings that regulatory B cell subgroups were reduced in AN and their strong relationship with body composition parameters point toward an impact of immunoregulatory B cells in the pathogenesis of AN.

Kurzzeitige Behandlung von Patient_innen mit Anorexia nervosa mit rekombinant hergestelltem Human-Leptin (Metreleptin): Rasch einsetzende positive Effekte auf Stimmung, Kognition und Verhalten - Hebebrand, Johannes; Antel, Jochen; Tan, Susanne; Wabitsch, Martin; Wiesing, Urban; Barth, Nikolaus; Ludwig, Christine; Bühlmeier, Judith; Libuda, Lars; Milos, Gabriella; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)

Impact of lunch with carbohydrates differing in glycemic index on children's cognitive functioning in the late postprandial phase: a randomized crossover study - Drozdowska, Alina; Sinningen, Kathrin; Falkenstein, Michael; Rudolf, Henrik; Libuda, Lars; Buyken, Anette; Lücke, Thomas; Kersting, Mathilde (European Journal of Nutrition)
Abstract Purpose Studies about effects of lunch dietary Glycemic Index (GI) on cognition of schoolchildren are scarce. Our previous CogniDo GI study found no changes of cognition in the early postprandial phase after consumption of two rice types with medium vs. high dietary GI for lunch (i.e., 45 min after starting lunch). This study investigated whether the dietary GI of lunch has an impact on cognition of schoolchildren in the late postprandial phase, 90 min after lunch. Methods A randomized, 2 × 2 crossover intervention study was conducted at a comprehensive school with 5th and 6th grade students. Participants ( n = 212) were randomly assigned to either sequence 1 or 2. In the first period, participants of sequence 1 received a dish with high GI rice (GI: 79), those of sequence 2 with medium GI rice (GI: 64)—in the second period, 1 week later, vice versa. Computer-based cognitive testing was performed 90 min after lunch examining tonic alertness, visual search and task switching, and working memory. Treatment effects and treatment effects adjusted for estimated lunch glycemic load (GL) were analyzed using a linear mixed model. Results The selected cognitive parameters were not affected by the GI of lunch 90 min after lunch, neither after intention-to-treat nor in the per-protocol analysis. Adjustment for GL also did not change results. Conclusion The present study revealed no notable differences after the consumption of two rice types with medium vs. high dietary GI for lunch in children’s cognitive function in the late postprandial phase, 90 min after lunch. Clinical trial registration German Clinical Trials Register (DRKS00013597); date of registration: 16/04/2018, retrospectively registered.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Wirtschaft ist Care ist radikale Demokratie - Tecklenburg, Feline (Dass die Welt wohnlich für alle wird. Klartexte, Anfragen, Perspektiven. Ina Praetorius zum 65. Geburtstag)

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Mapping postprandial responses sets the scene for targeted dietary advice - Brand-Miller, Jennie; Buyken, Anette (Nature Medicine)

Long‐term effects of hydrolyzed formulae on atopic diseases in the GINI study - Gappa, Monika; Filipiak‐Pittroff, Birgit; Libuda, Lars; Berg, Andrea; Koletzko, Sibylle; Bauer, Carl‐Peter; Heinrich, Joachim; Schikowski, Tamara; Berdel, Dietrich; Standl, Marie (Allergy)

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder - Libuda, Lars; Naaresh, Roaa; Ludwig, Christine; Laabs, Björn-Hergen; Antel, Jochen; Föcker, Manuel; Hebebrand, Johannes; Hinney, Anke; Peters, Triinu (European Journal of Nutrition)
Abstract Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide association study (GWAS) considering phenotype data from 79,366 individuals of European ancestry. Data on risk for ADHD were derived from a GWAS analysis with 20,183 individuals diagnosed with ADHD and 35,191 controls. For our analysis, we considered effect sizes based on the European participants (19,099 cases and 34,194 controls). Results Single SNP analyses showed a causal effect of vitamin D on ADHD risk for only one SNP (rs12785878, p = 0.024). The overall MR estimates did not reveal a causal effect of 25(OH)D on risk for ADHD. In the reverse analysis, neither any single nor the multi-SNP MR analyses showed a causal effect of ADHD on 25(OH)D. Conclusion Results from this two-sample MR study did not confirm a causal effect of 25(OH)D on ADHD or vice versa. Accordingly, our study does not provide evidence that improving 25(OH)D via supplementation could reduce the risk of developing ADHD.

The overall diet quality in childhood is prospectively associated with the timing of puberty - Duan, Ruonan; Qiao, Tian; Chen, Yue; Chen, Mengxue; Xue, Hongmei; Zhou, Xue; Yang, Mingzhe; Liu, Yan; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose The influences of nutrition in childhood on puberty onset could have sustained consequences for health and wellbeing later in life. The aim of this study was to investigate the prospective association of diet quality prior to puberty with the timing of puberty onset. Methods We considered data from 3983 SCCNG (Southwest China Childhood Nutrition and Growth) study participants with dietary data, anthropometric measurement, and information on potential confounders at their baseline assessment (mean age: 7.1 years for girls and 7.3 years for boys; mean length of follow-up was 4.2 years). Cox proportional hazard regression estimating hazard ratios (HRs) and 95% confidence intervals (CIs) were used to examine the relationship between diet quality and puberty onset. Dietary intake at baseline was assessed using a validated food frequency questionnaire. Diet quality was determined using the Chinese Children Dietary Index (CCDI) which measures adherence to current dietary recommendations (theoretical range: 0–160 points). Age at Tanner stage 2 for breast/genital development (B2/G2), menarche or voice break (M/VB) were used as pubertal markers. Results The CCDI score ranged from 56.2 to 136.3 for girls and 46.1–131.5 for boys. Pubertal markers consistently indicate that girls and boys with higher diet quality were more likely to enter their puberty later than their counterparts with lower CCDI scores (higher vs. lower CCDI tertiles: adjusted HR for age at B2: 0.85 (95% CI, 0.81–0.94), p for trend = 0.02; G2: 0.86 (95% CI,0.80–0.96), p for trend = 0.02; M: 0.86 (95% CI,0.80–0.95), p for trend = 0.02; VB: 0.86 (95% CI,0.79–0.98), p for trend = 0.03), after adjustment for paternal education level, baseline energy intake, and pre-pubertal body fat. Conclusions Our data suggested a later puberty onset and later timing of progressed puberty stages in children with a high diet quality, which were independent of pre-pubertal body fat.

Die Ernährungsversorgung in Familien zwischen Zeit, Alltag und Haushaltsführung. Eine Mixed-Methods-Untersuchung - Klünder, Nina

Der Jugendamts-Monitor. Aufgaben – Trends – Daten - Müller, Heinz; Klünder, Nina

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Short-term metreleptin treatment of patients with anorexia nervosa: rapid on-set of beneficial cognitive, emotional, and behavioral effects - Milos, Gabriella; Antel, Jochen; Kaufmann, Lisa-Katrin; Barth, Nikolaus; Koller, Antonia; Tan, Susanne; Wiesing, Urban; Hinney, Anke; Libuda, Lars; Wabitsch, Martin; von Känel, Roland; Hebebrand, Johannes (Translational Psychiatry)
Abstract To examine the hypothesis that normalization of low circulating leptin levels in patients with anorexia nervosa ameliorates hyperactivity, three seriously ill females with hyperactivity were treated off-label with metreleptin (recombinant human leptin) for up to 14 days. Drive for activity, repetitive thoughts of food, inner restlessness, and weight phobia decreased in two patients. Surprisingly, depression improved rapidly in all patients. No serious adverse events occurred. Due to obvious limitations of uncontrolled case series, placebo-controlled clinical trials are mandatory to confirm the observed rapid onset of beneficial effects. Our findings suggest an important role of hypoleptinemia in the mental and behavioral phenotype of anorexia nervosa.

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study - Peters, Triinu; Nüllig, Lena; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Tegeler, Lisa; Amhaouach, Chaima; Libuda, Lars; Hinney, Anke; Hebebrand, Johannes (Frontiers in Genetics)

Early changes in hepatic energy metabolism and lipid content in recent-onset type 1 and 2 diabetes mellitus - Kupriyanova, Yuliya; Zaharia, Oana Patricia; Bobrov, Pavel; Karusheva, Yanislava; Burkart, Volker; Szendroedi, Julia; Hwang, Jong-Hee; Roden, Michael; Roden, M.; Al-Hasani, H.; Burkart, V.; Buyken, Anette; et al. (Journal of Hepatology)

World trends in sugar-sweetened beverage and dietary sugar intakes in children and adolescents: a systematic review - Della Corte, Karen; Fife, Jessica; Gardner, Alexis; Murphy, Britta L; Kleis, Linda; Della Corte, Dennis; Schwingshackl, Lukas; LeCheminant, James D; Buyken, Anette (Nutrition Reviews)
Abstract Objective To provide a systematic overview of world dietary sugar and sugar-sweetened beverage (SSB) intake trends in children and adolescents. Data Sources Medline, Embase, and the Cochrane Central Register of Controlled Trials in the Cochrane Library were searched through January 2019 to identify longitudinal follow-up studies with time-trend data and repeated cross-sectional studies. Data Extraction Data from studies reporting ≥ 2 measurements (sugars, SSB, or sweets/candy) over ≥ 2 years and included ≥ 20 healthy, normal- or overweight children or adolescents aged 1–19 years. Data Analysis Data from 43 articles (n = 4 prospective cohort studies; n = 39 repeated cross-sectional studies) from 15 countries (n = 8 European countries plus Australia, Canada, China, South Korea, Mexico, Russia, and the United States) are presented narratively. According to the risk of bias in nonrandomized studies of interventions tool, 34 studies were judged to have a moderate risk of bias, and 5 to have a serious risk of bias. Conclusions Consumption among US children and adolescents increased substantially in the decades preceding 2000, followed by a faster and continued decline. As a whole, other international intake trends did not reveal drastic increases and decreases in SSB and dietary sugars; they tended to change only slightly across 3 decades.

Dietary Fibre Consensus from the International Carbohydrate Quality Consortium (ICQC) - Augustin, Livia S. A.; Aas, Anne-Marie; Astrup, Arnie; Atkinson, Fiona S.; Baer-Sinnott, Sara; Barclay, Alan W.; Brand-Miller, Jennie C.; Brighenti, Furio; Bullo, Monica; Buyken, Anette; Ceriello, Antonio; Ellis, Peter R.; et al. (Nutrients)
Dietary fibre is a generic term describing non-absorbed plant carbohydrates and small amounts of associated non-carbohydrate components. The main contributors of fibre to the diet are the cell walls of plant tissues, which are supramolecular polymer networks containing variable proportions of cellulose, hemicelluloses, pectic substances, and non-carbohydrate components, such as lignin. Other contributors of fibre are the intracellular storage oligosaccharides, such as fructans. A distinction needs to be made between intrinsic sources of dietary fibre and purified forms of fibre, given that the three-dimensional matrix of the plant cell wall confers benefits beyond fibre isolates. Movement through the digestive tract modifies the cell wall structure and may affect the interactions with the colonic microbes (e.g., small intestinally non-absorbed carbohydrates are broken down by bacteria to short-chain fatty acids, absorbed by colonocytes). These aspects, combined with the fibre associated components (e.g., micronutrients, polyphenols, phytosterols, and phytoestrogens), may contribute to the health outcomes seen with the consumption of dietary fibre. Therefore, where possible, processing should minimise the degradation of the plant cell wall structures to preserve some of its benefits. Food labelling should include dietary fibre values and distinguish between intrinsic and added fibre. Labelling may also help achieve the recommended intake of 14 g/1000 kcal/day.

Inflammatory mediators in the adipo-renal axis: leptin, adiponectin, and soluble ICAM-1 - Hua, Yifan; Herder, Christian; Kalhoff, Hermann; Buyken, Anette; Esche, Jonas; Krupp, Danika; Wudy, Stefan A.; Remer, Thomas (American Journal of Physiology-Renal Physiology)
A lower 24-h urine pH (24h-pH), i.e., a higher renal excretion of free protons, at a given acid load to the body, denotes a reduction in the kidney’s capacity for net acid excretion (NAE). There is increasing evidence, not only for patients with type 2 diabetes but also for healthy individuals, that higher body fatness or waist circumference (WC) has a negative impact on renal function to excrete acids (NAE). We hypothesized that adiposity-related inflammation molecules might mediate this relation between adiposity and renal acid excretion function. Twelve biomarkers of inflammation were measured in fasting blood samples from 162 adult participants (18–25 yr old) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had undergone anthropometric measurements and collected 24-h urine samples. Both Baron and Kenny’s (B&K’s) steps to test mediation and causal mediation analysis were conducted to examine the potential mediatory roles of biomarkers of inflammation in the WC-24-h pH relationship after strictly controlling for laboratory-measured NAE. In B&K’s mediation analysis, leptin, soluble intercellular adhesion molecule 1 (sICAM-1), and adiponectin significantly associated with the outcome 24-h pH and attenuated the WC-pH relation. In agreement herewith, causal mediation analysis estimated the “natural indirect effects” of WC on 24-h pH via leptin ( P = 0.01) and adiponectin ( P = 0.03) to be significant, with a trend for sICAM-1 ( P = 0.09). The calculated proportions mediated by leptin, adiponectin, and sICAM-1 were 64%, 23%, and 12%, respectively. Both mediation analyses identified an inflammatory cytokine (leptin) and an anti-inflammatory cytokine (adiponectin) along with sICAM-1 as being potentially involved in mediating adiposity-related influences on renal acid excretion capacity.

Early life factors and their relevance to intima-media thickness of the common carotid artery in early adulthood - Nyasordzi, Juliana; Penczynski, Katharina; Remer, Thomas; Buyken, Anette (PLOS ONE)

Reply to Khan et al. - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)

Sugar intake among German adolescents: trends from 1990 to 2016 based on biomarker excretion in 24-h urine samples - Perrar, Ines; Gray, Nicola; Kuhnle, Gunter G.; Remer, Thomas; Buyken, Anette; Alexy, Ute (British Journal of Nutrition)
Abstract Trend analyses based on dietary records suggest decreases in the intakes of total sugar (TS), added and free sugar since 2005 among children and adolescents in Germany. In terms of age trends, TS intake decreased with increasing age. However, self-reported sugar intake in epidemiological studies is criticised, as it may be prone to bias due to selective underreporting. Furthermore, adolescents are more susceptible to underreporting than children. We thus analysed time and age trends in urinary fructose excretion (FE), sucrose excretion (SE) and the sum of both (FE + SE) as biomarkers for sugar intake among 8·5–16·5-year-old adolescents. Urinary sugar excretion was measured by UPLC-MS/MS in 997 24-h urine samples collected from 239 boys and 253 girls participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study cohort between 1990 and 2016. Time and age trends of log-transformed FE, SE and FE + SE were analysed using polynomial mixed-effects regression models. Between 1990 and 2016, FE as well as FE + SE decreased (linear time trend: P = 0·0272 and P < 0·0001, respectively). A minor increase in excretion during adolescence was confined to FE (linear age trend: P = 0·0017). The present 24-h excretion measurements support a previously reported dietary record-based decline in sugar intake since 2005. However, the previously seen dietary record-based decrease in TS from childhood to late adolescence was not confirmed by our biomarker analysis, suggesting a constant sugar intake for the period of adolescence.

The Relationship between Glycemic Index and Health - Brand-Miller, Jennie; Buyken, Anette (Nutrients)
There is no question that elevated postprandial glycemia is a significant driver of common chronic diseases globally [...]

Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children’s cognitive function in a randomized crossover study - Jansen, Kathrin; Tempes, Jana; Drozdowska, Alina; Gutmann, Maike; Falkenstein, Michael; Buyken, Anette; Libuda, Lars; Rudolf, Henrik; Lücke, Thomas; Kersting, Mathilde (European Journal of Clinical Nutrition)

Kommunale Planung für Senior*innen bis 2025. Fortschreibung des Altenhilfeplans aus dem Jahr 2013

Psychische Auffälligkeiten bei Kindern und Jugendlichen, für die das Jugendamt in Anspruch genommen wurde - Wagenknecht, Inga; Meier-Gräwe, Uta (Praxis der Kinderpsychologie und Kinderpsychiatrie)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Age and time trends in sugar intake among children and adolescents: results from the DONALD study - Perrar, Ines; Schmitting, Sarah; Della Corte, Karen W.; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Is there a soft drink vs. alcohol seesaw? A cross-sectional analysis of dietary data in the Australian Health Survey 2011–12 - Wong, Tommy H. T.; Buyken, Anette; Brand-Miller, Jennie C.; Louie, Jimmy Chun Yu (European Journal of Nutrition)

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.